Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd004622.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Full-mouth disinfection for the treatment of adult chronic periodontitis

Abstract: In patients with chronic periodontitis in moderately deep pockets slightly more favourable outcomes for pocket reduction and gain in probing attachment were found following FMD compared to control. However, these additional improvements were only modest and there was only a very limited number of studies available for comparison, thus limiting general conclusions about the clinical benefit of full-mouth disinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 22 publications
1
55
0
5
Order By: Relevance
“…Carotid IMT measures the extent and severity of localized atherosclerosis in the carotid artery, 20 is independently 21 and is considered to be the best noninvasive marker of global burden of atherosclerosis. 22 Consistent with the pathophysiology of atherosclerosis, carotid IMT generally increases as people age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carotid IMT measures the extent and severity of localized atherosclerosis in the carotid artery, 20 is independently 21 and is considered to be the best noninvasive marker of global burden of atherosclerosis. 22 Consistent with the pathophysiology of atherosclerosis, carotid IMT generally increases as people age.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to short-term periodontal tissue responses, Cochrane systematic review evidence indicates that single sessions of non-surgical periodontal treatment yield comparable outcomes to multiple visits. 20 Therefore, it was not expected that the alteration from an intervention administered over two appointments would differ in terms of efficacy to an intervention administered in a single session, with regards to short-term changes in periodontal health.…”
Section: Expanded Discussionmentioning
confidence: 99%
“…Many papers and documents describing the efficacy of the "standard" full-mouth disinfection procedure are available in the literature Eberhard et al (2008) and Farman and Joshi (2008). Nevertheless, no documents are present, at the best of the authors' knowledge, dealing with the assessment of possible effects of an early application of a decontamination protocol on periodontal conditions at the time of SRP.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was not focused on testing the efficacy of the one-stage full-mouth disinfection procedure, which is already well documented (Eberhard et al, 2008;Farman and Joshi, 2008). The idea underlying the study was that bacterial load reduction was achieved with the application of the disinfection protocol proposed, consisting of tongue brushing and mouth rinsing with chlorhexidinebased products, at home, would accordingly lead to a decrease in swelling, pain sensitivity and especially bleeding, making the subsequent SRP procedure more comfortable for the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Richard (2008) observed that children with periodontal disease may likely come down with Protein Calorie Malnutrition which can even lead to death of the child as a result of poor feeding. Tomas et al (2012) also noted that bacteremia from gingival disease could lead to very fatal morbidity and even mortality while Ebehard (2008), Nguyen (2008), Humphrey (2008), and Popat et al (2008) all opined that tissue death (necrosis), halitosis, Coronary Heart Disease, and Rheumatic fever where other forms of morbidities arising from periodontal disease. Jacqueline et al (2002) also stated that periodontal disease can also lead to destruction of alveolar bone and eventual tooth loss.…”
Section: Introductionmentioning
confidence: 99%